Positive electrode material and preparation method thereof
By coating lithium vanadate on the core of the high-nickel ternary cathode material and doping a modified coating layer, combining hydrothermal method and secondary calcination preparation method, the cycle life and stability of the high-nickel cathode material are solved, and higher battery performance and longer service life are achieved.
Patent Information
- Application Number
- CN202311239512.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
High-nickel ternary cathode material has cycle life and stability problems in lithium-ion batteries, and it is easy to react with water and carbon dioxide in the air to form impurities during the preparation process, affecting battery performance.
The core of the positive electrode material is coated with lithium vanadate, and the coating layer is doped by modifying other metal elements, combined with hydrothermal method and secondary calcination preparation method, to ensure the uniformity and stability of the coating layer.
It effectively avoids direct contact between the core and the electrolyte, improves the cycle life and structural stability of the positive electrode material, and improves the electrochemical performance of the battery by improving the lithium ion diffusion channel.
Smart Images

Figure CN119695091A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of lithium-ion batteries, and in particular to a positive electrode material and a preparation method thereof. Background Art
[0002] The key core material of power batteries is the positive electrode material, which can be divided into single crystal positive electrode materials and polycrystalline positive electrode materials. There are a large number of grain boundaries in polycrystalline positive electrode materials. During the charging and discharging process of the battery, cracking easily occurs at the grain boundaries, which leads to an increase in the impedance of the battery and a decrease in the electrochemical performance. At present, the ternary positive electrode materials commonly used in lithium-ion batteries usually refer to nickel-cobalt-manganese ternary positive electrode materials. In this ternary positive electrode material, nickel, cobalt, and manganese are all transition metal elements that can form a solid solution. Increasing the content of nickel in the ternary positive electrode material can increase the battery capacity, but at the same time it will also reduce the cycle life and stability of the battery. In addition, during the preparation and storage process, high-nickel ternary positive electrode materials are more likely to react with water and carbon dioxide in the air to generate impurities such as LiOH and Li2CO3 than conventional ternary positive electrode materials, thereby affecting the cycle life of the battery. Therefore, a water washing process is usually added after the sintering of the high-nickel ternary positive electrode material to remove impurities such as LiOH and Li2CO3. Summary of the invention
[0003] In view of this, the present application provides a positive electrode material, which uses lithium vanadate to coat the core, effectively avoiding direct contact between the core and the electrolyte, improving its cycle life and structural stability; and the present application further improves the structural stability of the positive electrode material by doping and modifying the coating layer with other metal elements. The present application also provides a method for preparing the positive electrode material, which uses a hydrothermal method and secondary calcination to make the coating layer of the positive electrode material more uniform.
[0004] The first aspect of the present application provides a positive electrode material, the positive electrode material comprising a core and a coating layer coated on the surface of the core; the core comprises LiNi a Co b Mn c M1 d O2, wherein 0.8≤a≤0.98, 0≤b≤0.1, 0.02≤c≤0.2, 0≤d≤0.005, a+b+c+d=1; the coating layer includes Li x V2O yand a doping element M2, wherein 0≤x≤1, 4≤y≤5; wherein M1 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W; wherein M2 is selected from one or more of B, Mg, Al, Ca, Ti, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W.
[0005] In the embodiment of the present application, the M1 is selected from one or more of Zr, Al and W, and the M2 is selected from one or more of Ca, Al and Mg.
[0006] In the embodiment of the present application, the average primary particle size of the positive electrode material is 1 μm-10 μm.
[0007] In the implementation manner of the present application, the thickness of the coating layer is 5nm-50nm, and the mass of the coating layer is 0.15%-5% of the mass of the core.
[0008] In the embodiment of the present application, the mass of the doping element M2 in the coating layer is the Li x V2O y The V element accounts for 2%-10% of the mass.
[0009] The second aspect of the present application provides a method for preparing the positive electrode material provided in the first aspect of the present application, comprising the following steps:
[0010] The nickel source, the cobalt source, the manganese source, the core doping metal source and the lithium salt are mixed and calcined for the first time to synthesize the positive electrode material core;
[0011] The cathode material core, the coating layer doped metal source and the vanadium source solution are mixed, and the obtained mixed solution is subjected to a hydrothermal reaction under acidic conditions to obtain a cathode material precursor;
[0012] The positive electrode material precursor is dried, and then calcined for a second time to obtain the positive electrode material.
[0013] In the embodiment of the present application, the nickel source, cobalt source and manganese source include Ni a Co b Mn c (OH)2、Ni a Co b Mn c O2 or a mixture of NiO, CoO and MnO in a mass ratio of a:b:c, wherein 0.8≤a≤0.98, 0≤b≤0.1, 0.02≤c≤0.2, and a+b+c=1.
[0014] In the embodiment of the present application, the core doping metal source includes M1O x , wherein x is a number that satisfies the conservation of valence of the chemical formula, and M1 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W.
[0015] In an embodiment of the present application, the lithium salt includes LiOH and / or Li2CO3.
[0016] In the embodiment of the present application, the coating layer doping metal source includes M2Cl x 、M2(SO4) x and M2(NO3) x One or more of , wherein x is a number that satisfies the conservation of chemical valence, and M2 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W.
[0017] In the embodiment of the present application, the vanadium source solution includes vanadyl acetylacetonate and lithium metavanadate.
[0018] In an embodiment of the present application, the ratio of the sum of the masses of Ni, Co, and Mn elements in the nickel source, cobalt source, and manganese source to the mass of the Li element in the lithium salt is (Ni+Co+Mn):Li=1:1.01-1.1.
[0019] In an embodiment of the present application, the molar ratio of vanadium acetylacetonate to lithium metavanadate in the vanadium source solution is 1:1-1.3; the molar concentration of the lithium metavanadate in the vanadium source solution is 10mmol / L-80mmol / L; the mass of the lithium metavanadate in the mixed solution is 0.5%-5% of the mass of the core of the positive electrode material.
[0020] In the embodiment of the present application, the first calcination is a one-stage calcination or a two-stage calcination, the calcination temperature of the one-stage calcination is 780℃-950℃, the calcination time is 14h-20h, the heating rate is 5℃ / min-10℃ / min, and the calcination atmosphere is oxygen; the two-stage calcination includes pre-calcination and constant temperature calcination, the calcination atmosphere is oxygen, the pre-calcination temperature is 500℃-750℃, the pre-calcination time is 1h-6h, the constant temperature calcination temperature is 780℃-900℃, the constant temperature calcination time is 12h-20h, and the heating rate of the constant temperature calcination is 5℃ / min-10℃ / min.
[0021] In the embodiment of the present application, the calcination temperature of the second calcination is 350°C-700°C, the calcination time is 6h-18h, the heating rate is 5°C / min-10°C / min, and the calcination atmosphere is oxygen.
[0022] In the embodiment of the present application, the pH value of the mixed solution under the acidic conditions is 2-6; the reaction temperature of the hydrothermal reaction is 160°C-210°C, the reaction time is 12h-36h, and the heating rate is 5°C / min-10°C / min.
[0023] The third aspect of the present application provides a positive electrode material prepared by the preparation method provided by the second aspect of the present application.
[0024] The fourth aspect of the present application provides a battery positive electrode, including a conductive current collector and a positive electrode active material loaded on the conductive current collector, wherein the positive electrode active material includes the positive electrode material described in the first aspect or the positive electrode material obtained by the preparation method described in the second aspect of the present application.
[0025] A fifth aspect of the present application provides a battery, comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the positive electrode comprises the battery positive electrode as described in the third aspect.
[0026] A sixth aspect of the present application provides an electrical device, wherein the electrical device comprises the battery as described in the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram of the structure of a positive electrode material provided in one embodiment of the present application;
[0028] Figure 2 A flow chart of a method for preparing a positive electrode material provided in this application.
[0029] Description of Figure Numbers
[0030] 100-positive electrode material; 101-core; 102-coating layer. DETAILED DESCRIPTION
[0031] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.
[0032] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.
[0033] The key core material of power batteries is the positive electrode material, which can be divided into single crystal positive electrode materials and polycrystalline positive electrode materials. There are a large number of grain boundaries in polycrystalline positive electrode materials. During the charging and discharging process of the battery, cracking is likely to occur at the grain boundaries, which will lead to an increase in the impedance of the battery and a decrease in the electrochemical performance. At present, the commonly used ternary positive electrode materials in lithium-ion batteries usually refer to nickel-cobalt-manganese ternary positive electrode materials. In this ternary positive electrode material, nickel, cobalt, and manganese are all transition metal elements that can form a solid solution. Increasing the content of nickel in the ternary positive electrode material can increase the battery capacity, but at the same time it will also reduce the cycle life and stability of the battery. In particular, high-nickel ternary positive electrode materials with a nickel metal content of more than 80% are usually faced with the problem of Ni 3+ Various side reactions caused by intrinsic instability eventually lead to the collapse of the material structure, surface passivation and significant capacity attenuation when lithium ions are deintercalated. In order to improve the cycle life and stability of high-nickel ternary positive electrode materials, the prior art discloses coating the surface of high-nickel ternary positive electrode material substrates with vanadium pentoxide, lithium molybdate and other substances, but the coating growth of vanadium pentoxide is uncontrollable, and vanadium pentoxide cannot provide a lithium source, which affects the capacity release. Lithium molybdate has an orthogonal structure, which is not well matched with the layered structure of the high-nickel ternary positive electrode material substrate, and there is a risk of affecting the growth of the coating layer and the diffusion of lithium ions.
[0034] In addition, during the preparation and storage process, high-nickel ternary positive electrode materials are more likely to react with water and carbon dioxide in the air to generate impurities such as LiOH and Li2CO3 than conventional ternary positive electrode materials, thereby affecting the cycle life of the battery. Therefore, a water washing process is usually added after the high-nickel ternary positive electrode materials are sintered to remove impurities such as LiOH and Li2CO3.
[0035] In view of the above problems, the present application provides a positive electrode material, which includes a core and a lithium vanadate coating layer coated on the surface of the core, effectively avoiding direct contact between the core of the positive electrode material and the electrolyte, and improving its cycle life and structural stability. In addition, the present application further improves the structural stability of the positive electrode material by doping and modifying the core and coating of the positive electrode material with other metal elements.
[0036] See also Figure 1 The present application provides a positive electrode material 100, which includes a core 101 and a coating layer 102 coated on the surface of the core 101. The core 101 of the positive electrode material includes LiNi a Co b Mn c M1 dO2, wherein 0.8≤a≤0.98, 0≤b≤0.1, 0.02≤c≤0.2, 0≤d≤0.005, a+b+c+d=1. The present application selects a high nickel ternary positive electrode material with a nickel content greater than or equal to 80% as the substrate of the core 101, and increases the energy density of the positive electrode material 100 by increasing the nickel content.
[0037] In the embodiments of the present application, M1 is a doping element of the core 101, and the doping element M1 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W. The present application improves the stability of the core 101 by doping and modifying the core 101 of the positive electrode material with the doping element M1. In some embodiments of the present application, the doping element M1 in the core 101 is selected from one or more of Zr, Al and W. Zr, Al and W can form extremely stable Al-O, WO, Zr-O bonds with oxygen atoms, and no redox changes occur during battery operation, which can better improve the structural stability of the positive electrode material. The doping element M1 in the core 101 can be a single element doping the core 101, or multiple elements can co-dope the core 101, wherein the synergistic effect of co-doping of multiple elements can comprehensively improve and improve the comprehensive performance of the positive electrode material. In some embodiments of the present application, the doping element M1 may be, for example, Zr. The larger ionic radius and stronger Zr-O bond energy of the doping element Zr increase the interlayer spacing of the core material and stabilize the crystal structure, increase the lithium ion diffusion coefficient, and improve the cycle performance of the battery. In other embodiments of the present application, the doping element M1 may be, for example, Zr and Al. The doping of a certain amount of Al element may also improve the structural stability and thermal stability of the core material. By adding Zr and Al at the same time, the two doping elements work synergistically to obtain a positive electrode core material with both excellent cycle performance and stability.
[0038] In the embodiment of the present application, the coating layer 102 includes Li x V2O yand doping element M2, wherein 0≤x≤1, 4≤y≤5, and doping element M2 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W. In the present application, the core 101 of the positive electrode material is coated with lithium vanadate. On the one hand, the coating layer 102 effectively isolates the active surface of the core 101 from direct contact with air, water and electrolyte, and minimizes the electrolyte side reaction, thereby improving the structural stability and cycle life of the positive electrode material 100; on the other hand, lithium vanadate, as a nano fast ion conductor, provides a fast lithium ion diffusion channel, providing the positive electrode material with good lithium ion conductivity. And the lithium vanadate coating layer can provide a lithium source for the core of the positive electrode material, thereby compensating for the irreversible consumption of Li in the SEI film to a certain extent, and further improving the electrochemical performance of the positive electrode material. In addition, the present application further improves the stability and rate performance of the positive electrode material 100 by doping the coating layer 102 with the doping element M2. In some embodiments of the present application, after the coating layer 102 is doped with M2, the transition metal layer spacing (002) of the coating layer 102 is changed from Increase to The coating layer 102 has a larger interplanar spacing, further improving the electrochemical performance of the material.
[0039] In some embodiments of the present application, the doping element M2 in the coating layer 102 is selected from one or more of Ca, Al and Mg. The doping element M2 in the coating layer 102 can be a single element doping, or it can be a co-doping of multiple elements. In some embodiments of the present application, the doping element M2 can be Al. The doping element Al forms a strong Al-O bond, which can better improve the structural stability of the coating layer lattice, thereby improving the electrochemical performance of the positive electrode material. In some embodiments of the present application, the doping element M2 can also be Ca or Mg. The Ca or Mg elements can be embedded in the coating layer structure, occupying the Li x V2O y The interlayer Li sites expand the interlayer spacing of the coating layer and stabilize the layered structure of the coating layer. In other embodiments of the present application, the doping element M2 can be, for example, co-doped with Al and Ca or co-doped with Al and Mg. The co-doping of the two elements can better comprehensively improve the structural stability and thermal stability of the positive electrode material coating layer.
[0040] In some specific embodiments of the present application, the doping element M1 can be Zr and Al, and the doping element M2 can be Al and Ca. By selecting appropriate doping elements for the positive electrode material core 101 and the coating layer 102 at the same time, multiple elements are co-doped. There is a synergistic effect between the doping elements M1 of the core 101, between the doping elements M2 of the coating layer 102, and between the doping elements M1 of the core 101 and the doping elements M2 of the coating layer 102, thereby comprehensively improving and enhancing the comprehensive performance of the positive electrode material 100.
[0041] In the embodiment of the present application, the average primary particle size of the positive electrode material is 1μm-10μm. The primary particle size is a concept relative to the secondary particle size of the particles after agglomeration, which is the original particle size of a single fine grain. In some embodiments, the average primary particle size of the positive electrode material can be 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 6μm, 8μm, 10μm. In some specific embodiments, the average primary particle size of the positive electrode material 100 can be 1μm-5μm. In some specific embodiments, the average primary particle size of the positive electrode material 100 can be 1μm-3μm. The positive electrode material of the present application is a single crystal structure with an average primary particle size in the range of 1μm-10μm. Compared with polycrystalline positive electrode materials with a large number of grain boundaries, the single crystal structure can effectively reduce grain boundaries, thereby reducing side reactions, increasing the compaction density of the material, thereby increasing the energy density of the battery, and increasing the cycle life of the battery.
[0042] In the embodiment of the present application, the thickness of the coating layer 102 is 5nm-50nm. In some embodiments, the thickness of the coating layer 102 can be, for example, 5nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm, 24nm, 25nm, 28nm, 30nm, 35nm, 40nm, 50nm. In some specific embodiments, the thickness of the coating layer 102 can be 10nm-40nm. In some specific embodiments, the thickness of the coating layer 102 can be 10nm-30nm. In the embodiment of the present application, the mass of the coating layer 102 is 0.15%-5% of the mass of the core 101. In some embodiments, the mass of the coating layer 102 can be, for example, 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% of the mass of the core 101. In some specific embodiments, the mass of the coating layer 102 can be 0.2%-2% of the mass of the core 101. In some specific embodiments, the mass of the coating layer 102 can be 0.2%-1% of the mass of the core 101. The present application controls the thickness and mass of the coating layer within a suitable range, which can ensure that the coating and isolation effect of the coating layer is good, and to a certain extent avoid the problem of reduced lithium ion insertion and extraction kinetics caused by the coating layer being too thick, thereby reducing the discharge specific capacity of the material.
[0043] In the embodiment of the present application, the mass of the doping element M2 in the coating layer 102 is Li x V2O y In some embodiments, the mass of the doping element M2 in the coating layer 102 may be, for example, Li x V2O y 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% of the mass of the V element in the coating layer 102. In some embodiments, the mass of the doping element M2 in the coating layer 102 may be Li x V2O y The amount of V in the coating layer is 5%-8% by mass. The present application controls the doping amount of the doping element in the coating layer within a suitable range, thereby avoiding the problems of insignificant performance improvement due to too little doping and affecting lithium ion diffusion due to too much doping, and obtaining a positive electrode material with excellent structural stability and electrochemical performance.
[0044] The positive electrode material provided in the present application is coated with lithium vanadate on the core of the positive electrode material. The lithium vanadate coating layer can reduce the electrolyte side reaction caused by direct contact between the core and the electrolyte, thereby improving the stability and cycle life of the positive electrode material; on the other hand, it can provide a fast lithium ion diffusion channel for the positive electrode material, thereby improving the lithium ion conductivity of the battery. In addition, the present application further improves the structural stability of the positive electrode material by doping and modifying the core of the positive electrode material and the lithium vanadate coating layer.
[0045] See also Figure 2 , Figure 2 The flowchart of the method for preparing the positive electrode material provided in the present application. The method for preparing the positive electrode material provided in the present application comprises the following steps:
[0046] S101, mixing a nickel source, a cobalt source, a manganese source, a core doping metal source and a lithium salt and calcining them for the first time to synthesize a positive electrode material core;
[0047] S102, mixing the cathode material core, the coating layer doped metal source and the vanadium source solution, and subjecting the obtained mixed solution to a hydrothermal reaction under acidic conditions to obtain a cathode material precursor;
[0048] S103, drying the positive electrode material precursor, and then calcining it for the second time to obtain the positive electrode material.
[0049] In the embodiment of the present application, the nickel source, the cobalt source, and the manganese source in step S101 include Ni a Co b Mn c (OH)2、Ni a Co b Mn c O2 or a mixture of NiO, CoO and MnO in a mass ratio of a:b:c, wherein 0.8≤a≤0.98, 0≤b≤0.1, 0.02≤c≤0.2, and a+b+c=1. a Co b Mn c (OH)2 can be synthesized by coprecipitation. In the present embodiment, Ni a Co b Mn c O2 can be synthesized by calcining the hydroxide of one or more elements of nickel, cobalt, and manganese. The present application selects a suitable nickel source, cobalt source, and manganese source and controls the content of each element in the nickel source, cobalt source, and manganese source to calcine a positive electrode material core with a high nickel content. The nickel content in the positive electrode material core is greater than or equal to 80%, so that the obtained positive electrode material has a higher energy density.
[0050] In the embodiment of the present application, the core is doped with a metal source M1Ox , wherein x is a number that satisfies the conservation of chemical valence, and M1 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W. In the embodiment of the present application, the core doping metal source M1O x It can be a combination of one or more, and the core doping metal source corresponding to the appropriate doping element can be selected according to the actual performance requirements. In some embodiments of the present application, the core doping metal source M10 x For example, it can be one or more of ZrO2, MgO, Al2O3, CaO, and TiO2. The application selects a core doping metal source to dope and modify the core to improve the problem of decreased thermal stability and decreased cycle life caused by increased nickel content.
[0051] In the embodiments of the present application, the lithium salt includes LiOH and / or Li2CO3. In some embodiments of the present application, the lithium salt may be LiOH, Li2CO3 or a mixture of the two.
[0052] In the embodiment of the present application, the first calcination is a one-stage calcination or a two-stage calcination. In some embodiments of the present application, the first calcination can be a one-stage calcination, the calcination temperature of the one-stage calcination is 780°C-950°C, the calcination time is 14h-20h, the heating rate is 5°C / min-10°C / min, and the calcination atmosphere is oxygen. In some embodiments of the present application, the calcination temperature of the one-stage calcination can be 780°C, 800°C, 820°C, 8400°C, 850°C, 860°C, 880°C, 900°C, 930°C, 950°C, the calcination time can be 14h, 15h, 16h, 17h, 18h, 19h, 20h, the heating rate can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, and the calcination atmosphere can be oxygen.
[0053] In some embodiments of the present application, the first calcination can be a two-stage calcination, the two-stage calcination includes pre-calcination and constant temperature calcination, the calcination atmosphere is oxygen, the pre-calcination temperature is 500℃-750℃, the pre-calcination time is 1h-6h, the constant temperature calcination temperature is 780℃-900℃, the constant temperature calcination time is 12h-20h, and the constant temperature calcination heating rate is 5℃ / min-10℃ / min. In some embodiments of the present application, the pre-burning temperature in the two-stage calcination can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, and the pre-burning time can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 5h, 6h, the temperature of constant temperature calcination can be 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 850°C, 880°C, 890°C, 900°C, the time of constant temperature calcination can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, and the heating rate of constant temperature calcination can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. In some specific embodiments of the present application, the pre-burning temperature in the two-stage calcination can be 600°C-750°C, the pre-burning time is 1h-4h, the constant temperature calcination temperature is 780°C-850°C, and the constant temperature calcination time is 12h-18h. Further, the pre-burning temperature in the two-stage calcination can be 700°C-750°C, the pre-burning time is 2h-4h, the constant temperature calcination temperature is 800°C-830°C, and the constant temperature calcination time is 12h-16h. In some embodiments of the present application, setting the first calcination as a two-stage calcination can make the core of the positive electrode material sintered more fully, and obtain a single crystal structure with high stability and high cycle life. The present application controls the temperature and time of the first calcination within a reasonable range, which is conducive to the full sintering of the material and obtains the core of the positive electrode material with a single crystal structure. Compared with polycrystalline positive materials with a large number of grain boundaries, the single crystal structure can effectively reduce the grain boundaries, thereby reducing side reactions, increasing the compaction density of the material, thereby increasing the energy density of the battery, and increasing the cycle life of the battery.
[0054] In the embodiment of the present application, the nickel source, the cobalt source, the manganese source, the core doping metal source and the lithium salt can be mixed evenly using a ball mill or a high-speed mixer.
[0055] In the embodiment of the present application, the coating layer doping metal source in step S102 includes M2Cl x 、M2(SO4) x and M2(NO3) xOne or more of, wherein x is a number that satisfies the conservation of valence of the chemical formula, and M2 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W. In some embodiments of the present application, the coating layer doping metal source may be, for example, AlCl3, TiCl4 or YCl3. The selection of the coating layer doping metal source is selected according to the doping elements required for the actual coating layer, and may be a compound or a combination of multiple compounds. The purpose of adding the coating layer doping metal source is to achieve doping modification of the coating layer and surface ion exchange of the core of the positive electrode material.
[0056] In the embodiment of the present application, the vanadium source solution includes vanadium acetylacetonate and lithium metavanadate. The metavanadate in the vanadium source solution of the present application is selected from lithium metavanadate, which can eventually generate a lithium vanadate coating layer, which can provide a lithium source for the core of the positive electrode material, thereby compensating for the irreversible consumption of Li in the SEI film to a certain extent, and further improving the electrochemical performance of the positive electrode material.
[0057] In the embodiment of the present application, the ratio of the sum of the mass of Ni, Co, and Mn elements in the nickel source, cobalt source, and manganese source to the mass of Li element in the lithium salt is (Ni+Co+Mn):Li=1:1.01-1.1. In some embodiments, the ratio of the sum of the mass of Ni, Co, and Mn elements in the nickel source, cobalt source, and manganese source to the mass of Li element in the lithium salt can be (Ni+Co+Mn):Li=1:1.01, (Ni+Co+Mn):Li=1:1.02, (Ni+Co+Mn):Li=1:1.03, (Ni+Co+Mn):Li=1:1.05, (Ni+Co+Mn):Li=1:1.06, (Ni+Co+Mn):Li=1:1.08, (Ni+Co+Mn):Li=1:1.1.
[0058] In the embodiment of the present application, the molar ratio of vanadium acetylacetonate to lithium metavanadate in the vanadium source solution is 1:1-1.3; the molar concentration of the lithium metavanadate in the vanadium source solution is 10mmol / L-80mmol / L; the mass of the lithium metavanadate in the mixed solution is 0.5%-5% of the mass of the core of the positive electrode material. In some embodiments, the molar ratio of vanadium acetylacetonate to lithium metavanadate in the vanadium source solution can be 1:1, 1:1.1, 1:1.2, 1:1.3; the molar concentration of lithium metavanadate in the vanadium source solution can be 10mmol / L, 20mmol / L, 25mmol / L, 30mmol / L, 40mmol / L, 50mmol / L, 60mmol / L, 70mmol / L, 80mmol / L; the mass of the lithium metavanadate in the mixed solution can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% of the mass of the core of the positive electrode material. In some specific embodiments, the molar concentration of lithium metavanadate in the vanadium source solution can be 20mmol / L-60mmol / L, and the mass of lithium metavanadate in the mixed solution can be 1%-4% of the mass of the core of the positive electrode material. In some specific embodiments, the molar concentration of lithium metavanadate in the vanadium source solution can be 20mmol / L-40mmol / L, and the mass of lithium metavanadate in the mixed solution can be 1%-3% of the mass of the core of the positive electrode material. The present application controls the addition amount of lithium metavanadate within a suitable range, and can further control the thickness of the coating layer within a suitable range to avoid it being too thin or too thick to affect the electrochemical properties of the positive electrode material.
[0059] In the embodiment of the present application, the pH value of the mixed solution under acidic conditions is 2-6. In some embodiments, the pH value of the mixed solution under acidic conditions can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6. In some specific embodiments, the pH value of the mixed solution under acidic conditions can be 3-6. In some specific embodiments, the pH value of the mixed solution under acidic conditions can be 4-6. The present application sets the environment of the hydrothermal reaction under acidic conditions, which can react with impurities such as LiOH and Li2CO3, eliminating the subsequent step of washing the positive electrode material, shortening the process flow and reducing production costs.
[0060] In the embodiment of the present application, the reaction temperature of the hydrothermal reaction is 160°C-210°C, the reaction time is 12h-36h, and the heating rate is 5°C / min-10°C / min. In some embodiments, the temperature of the hydrothermal reaction can be 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, and the reaction time can be 12h, 13h, 14h, 15h, 16h, 18h, 20h, 22h, 24h, 25h, 28h, 30h, 32h, 35h, 36h, and the heating rate can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. In some specific embodiments, the temperature of the hydrothermal reaction can be 160°C-200°C, and the reaction time can be 12h-24h. The present application reasonably regulates the temperature and time of the hydrothermal reaction so that the lithium vanadate coating layer can evenly and fully cover the surface of the core of the positive electrode material.
[0061] In the embodiment of the present application, the calcination temperature of the second calcination in step S103 is 350°C-700°C, the calcination time is 6h-18h, the heating rate is 5°C / min-10°C / min, and the calcination atmosphere is oxygen. In some embodiments of the present application, the calcination temperature of the second calcination can be 350°C, 400°C, 450°C, 480°C, 500°C, 500°C, 550°C, 560°C, 580°C, 600°C, 650°C, 700°C, the calcination time can be 6h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 18h, and the heating rate can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. In some specific embodiments of the present application, the calcination temperature of the second calcination can be 400°C-600°C, and the calcination time is 8h-14h. In some specific embodiments of the present application, the calcination temperature of the second calcination can be 500°C-600°C, and the calcination time is 10h-14h. The present application controls the temperature and time of the second calcination within a suitable range, and a more uniform coating layer can be obtained on the surface of the core of the positive electrode material, further improving the cycle stability of the material.
[0062] In the embodiments of the present application, the drying process may be freeze drying or baking drying of the cathode material precursor obtained after the hydrothermal reaction. In some embodiments of the present application, freeze drying is selected as the drying process. After the cathode material precursor is freeze dried to remove the surface moisture of the material, it does not need to be ground and can be directly calcined, which has less damage to the coating layer of the cathode material.
[0063] The preparation method of the positive electrode material provided in the present application adopts a hydrothermal method and secondary calcination, so that the lithium vanadate coating layer of the prepared positive electrode material is more uniform, which can better avoid the contact between the core of the positive electrode material and the electrolyte, and further improve the structural stability of the material. In addition, the preparation method is an acidic solution environment, which can effectively remove impurities such as LiOH and Li2CO3, and further improve the service life of the battery.
[0064] The present application also provides a positive electrode material prepared by the preparation method described above.
[0065] The present application also provides a battery positive electrode, which includes a conductive current collector and a positive electrode active material loaded on the conductive current collector, and the positive electrode active material includes the positive electrode material provided above or the positive electrode material prepared by the preparation method described above.
[0066] The present application also provides a battery, which includes a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, and the positive electrode includes the battery positive electrode provided above.
[0067] The present application also provides an electric device, which includes the battery provided above. The electric device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.
[0068] The present application is further described below in multiple embodiments:
[0069] Example 1
[0070] 70g of Ni9Co 0.6 Mn 0.4 (OH)2, 32.5g LiOH and 0.3g ZrO2 were mixed, mixed evenly in a high-speed mixer and put into a box furnace for the first calcination. The calcination conditions were in an oxygen environment, with a pre-sintering temperature of 600°C, a pre-sintering time of 3h, a constant temperature calcination temperature of 850°C, a constant temperature calcination time of 12h, a heating rate of 5°C / min, and the core of the positive electrode material was collected after gas crushing;
[0071] 80 mg of AlCl3 was added to a mixed solution of 50 mL of a lithium metavanadate solution with a molar concentration of 30 mmol / L and 50 mL of a vanadyl acetylacetonate solution with a molar concentration of 30 mmol / L, and the pH of the mixed solution was adjusted to 5.5 with hydrochloric acid, 50 g of a cathode material core was added to the mixed solution, and after being fully and uniformly mixed by ultrasound or vibration, the solution was placed in a high-pressure reactor for hydrothermal reaction, and the reaction temperature of the hydrothermal reaction was 180 ° C, the reaction time was 14 h, and the heating rate was 5 ° C / min;
[0072] The positive electrode material precursor solid after hydrothermal treatment was collected by centrifugation, and was repeatedly washed and centrifuged three or more times with ultrapure water. The powder was collected after freeze-drying, and the powder was calcined for a second time in a box furnace to remove crystal water. The second calcination conditions were in an oxygen environment, the calcination temperature was 550°C, the calcination time was 12h, and the heating rate was 5°C / min, and finally the positive electrode material was obtained.
[0073] Example 2
[0074] 70g of Ni9Co 0.6 Mn 0.4 (OH)2, 32.5g LiOH and 0.3g ZrO2 were mixed, mixed evenly in a high-speed mixer and put into a box furnace for the first calcination. The calcination conditions were in an oxygen environment, with a pre-sintering temperature of 600°C, a pre-sintering time of 3h, a constant temperature calcination temperature of 850°C, a constant temperature calcination time of 12h, a heating rate of 5°C / min, and the core of the positive electrode material was collected after gas crushing;
[0075] 66 mg of TiCl4 was added to a mixed solution of 50 mL of a lithium metavanadate solution with a molar concentration of 30 mmol / L and 50 mL of a vanadyl acetylacetonate solution with a molar concentration of 30 mmol / L, and the pH of the mixed solution was adjusted to 5.5 with hydrochloric acid, 50 g of a cathode material core was added to the mixed solution, and after being fully and uniformly mixed by ultrasound or vibration, the solution was placed in a high-pressure reactor for hydrothermal reaction, and the reaction temperature of the hydrothermal reaction was 180°C, the reaction time was 14 h, and the heating rate was 5°C / min;
[0076] The positive electrode material precursor solid after hydrothermal treatment was collected by centrifugation, and was repeatedly washed and centrifuged three or more times with ultrapure water. The powder was collected after freeze-drying, and the powder was calcined for a second time in a box furnace to remove crystal water. The second calcination conditions were in an oxygen environment, the calcination temperature was 550°C, the calcination time was 12h, and the heating rate was 5°C / min, and finally the positive electrode material was obtained.
[0077] Example 3
[0078] 70g of Ni9Co 0.6 Mn 0.4 (OH)2, 32.5g LiOH and 0.3g ZrO2 were mixed, mixed evenly in a high-speed mixer and put into a box furnace for the first calcination. The calcination conditions were in an oxygen environment, with a pre-sintering temperature of 600°C, a pre-sintering time of 3h, a constant temperature calcination temperature of 850°C, a constant temperature calcination time of 12h, a heating rate of 5°C / min, and the core of the positive electrode material was collected after gas crushing;
[0079] 40 mg of YCl3 was added to a mixed solution of 50 mL of a lithium metavanadate solution with a molar concentration of 30 mmol / L and 50 mL of a vanadyl acetylacetonate solution with a molar concentration of 30 mmol / L, and the pH of the mixed solution was adjusted to 5.5 with hydrochloric acid, 50 g of a cathode material core was added to the mixed solution, and after being fully and uniformly mixed by ultrasound or vibration, the solution was placed in a high-pressure reactor for hydrothermal reaction, and the reaction temperature of the hydrothermal reaction was 180 ° C, the reaction time was 14 h, and the heating rate was 5 ° C / min;
[0080] The positive electrode material precursor solid after hydrothermal treatment was collected by centrifugation, and was repeatedly washed and centrifuged three or more times with ultrapure water. The powder was collected after freeze-drying, and the powder was calcined for a second time in a box furnace to remove crystal water. The second calcination conditions were in an oxygen environment, the calcination temperature was 550°C, the calcination time was 12h, and the heating rate was 5°C / min, and finally the positive electrode material was obtained.
[0081] Example 4
[0082] 70g of Ni9Co 0.6 Mn 0.4 (OH)2, 32.5g LiOH and 0.3g ZrO2 were mixed, mixed evenly in a high-speed mixer and put into a box furnace for the first calcination. The calcination conditions were in an oxygen environment, with a pre-sintering temperature of 600°C, a pre-sintering time of 3h, a constant temperature calcination temperature of 850°C, a constant temperature calcination time of 12h, a heating rate of 5°C / min, and the core of the positive electrode material was collected after gas crushing;
[0083] 80 mg of AlCl3 and 44 mg of CaCl2 were added to a mixed solution of 50 mL of a lithium metavanadate solution with a molar concentration of 30 mmol / L and 50 mL of a vanadyl acetylacetonate solution with a molar concentration of 30 mmol / L, and the pH of the mixed solution was adjusted to 5.5 with hydrochloric acid, 50 g of a cathode material core was added to the mixed solution, and after being fully and uniformly mixed by ultrasound or vibration, the solution was placed in a high-pressure reactor for hydrothermal reaction, and the reaction temperature of the hydrothermal reaction was 180°C, the reaction time was 14 h, and the heating rate was 5°C / min;
[0084] The positive electrode material precursor solid after hydrothermal treatment was collected by centrifugation, and was repeatedly washed and centrifuged three or more times with ultrapure water. The powder was collected after freeze-drying, and the powder was calcined for a second time in a box furnace to remove crystal water. The second calcination conditions were in an oxygen environment, the calcination temperature was 550°C, the calcination time was 12h, and the heating rate was 5°C / min, and finally the positive electrode material was obtained.
[0085] Example 5
[0086] 70g of Ni9Co 0.6 Mn0.4 (OH)2, 32.5g of LiOH, 0.3g of ZrO2, and 0.4g of Al2O3 were mixed, mixed evenly in a high-speed mixer, and then put into a box furnace for the first calcination. The calcination conditions were in an oxygen environment, with a pre-sintering temperature of 600°C, a pre-sintering time of 3h, a constant temperature calcination temperature of 850°C, a constant temperature calcination time of 12h, a heating rate of 5°C / min, and the core of the positive electrode material was collected after gas crushing;
[0087] 80 mg of AlCl3 and 44 mg of CaCl2 were added to a mixed solution of 50 mL of a lithium metavanadate solution with a molar concentration of 30 mmol / L and 50 mL of a vanadyl acetylacetonate solution with a molar concentration of 30 mmol / L, and the pH of the mixed solution was adjusted to 5.5 with hydrochloric acid, 50 g of a cathode material core was added to the mixed solution, and after being fully and uniformly mixed by ultrasound or vibration, the solution was placed in a high-pressure reactor for hydrothermal reaction, and the reaction temperature of the hydrothermal reaction was 180°C, the reaction time was 14 h, and the heating rate was 5°C / min;
[0088] The positive electrode material precursor solid after hydrothermal treatment was collected by centrifugation, and was repeatedly washed and centrifuged three or more times with ultrapure water. The powder was collected after freeze-drying, and the powder was calcined for a second time in a box furnace to remove crystal water. The second calcination conditions were in an oxygen environment, the calcination temperature was 550°C, the calcination time was 12h, and the heating rate was 5°C / min, and finally the positive electrode material was obtained.
[0089] Comparative Example 1
[0090] 70g of Ni9Co 0.6 Mn 0.4 (OH)2, 32.5g of LiOH and 0.3g of ZrO2 were mixed, mixed evenly in a high-speed mixer and then put into a box furnace for the first calcination. The calcination conditions were as follows: in an oxygen environment, the pre-calcination temperature was 600°C, the pre-calcination time was 3h, the constant temperature calcination temperature was 850°C, the constant temperature calcination time was 12h, and the heating rate was 5°C / min to obtain the positive electrode material.
[0091] Comparative Example 2
[0092] 70g of Ni9Co 0.6 Mn 0.4 (OH)2, 32.5g LiOH and 0.3g ZrO2 were mixed, mixed evenly in a high-speed mixer and put into a box furnace for the first calcination. The calcination conditions were in an oxygen environment, with a pre-sintering temperature of 600°C, a pre-sintering time of 3h, a constant temperature calcination temperature of 850°C, a constant temperature calcination time of 12h, a heating rate of 5°C / min, and the core of the positive electrode material was collected after gas crushing;
[0093] 50 mL of a lithium metavanadate solution with a molar concentration of 30 mmol / L and 50 mL of a vanadyl acetylacetonate solution with a molar concentration of 30 mmol / L were mixed, and the pH of the mixed solution was adjusted to 5.5 with hydrochloric acid. 50 g of the positive electrode material core was added to the mixed solution, and after being fully and uniformly mixed by ultrasound or vibration, it was placed in a high-pressure reactor for hydrothermal reaction. The reaction temperature of the hydrothermal reaction was 180°C, the reaction time was 14 h, and the heating rate was 5°C / min.
[0094] The positive electrode material precursor solid after hydrothermal treatment was collected by centrifugation, and was repeatedly washed and centrifuged three or more times with ultrapure water. The powder was collected after freeze-drying, and the powder was calcined for a second time in a box furnace to remove crystal water. The second calcination conditions were in an oxygen environment, the calcination temperature was 550°C, the calcination time was 12h, and the heating rate was 5°C / min, and finally the positive electrode material was obtained.
[0095] Performance Testing
[0096] The positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-2 were assembled into CR2016 button-type half-cells for electrochemical performance testing. N-methylpyrrolidone was used as a solvent to prepare the battery slurry, the binder was polyvinylidene fluoride, the conductive agent was acetylene black, and the mass ratio of the various components in the slurry was: active material / binder / conductive agent = 9 / 0.5 / 0.5. The battery slurry was evenly coated on aluminum foil and vacuum dried. In a glove box, the positive electrode sheet obtained after cutting and pressing was converted into a button cell with a lithium sheet negative electrode, a diaphragm, an electrolyte, and a gasket shrapnel group.
[0097] The electrochemical test of the button cell was performed using the button cell test channel of Xinwei. The test conditions used in the capacity test were a test window of 2.5V-4.3V, a charging current of 0.1C, a 4.3V constant voltage charge cut-off current of 0.01C, a discharge current of 0.1C, and an average value of two cycles. The charge and discharge current in the cycle test was 1C, and the test window was 2.5V-4.3V. All electrochemical test temperatures were 25°C in an air environment. The results are shown in Table 1.
[0098] Table 1 Structure and electrochemical performance test results of Examples 1-5 and Comparative Examples 1-2
[0099]
[0100] It can be seen from the data of Examples 1-5 and Comparative Examples 1-2 in Table 1 that the doped coated modified positive electrode material provided by the present application has a corresponding improvement in battery capacity and cycle performance compared to Comparative Example 1 in which no coating modification is performed and Comparative Example 2 in which the coating layer is not doped and modified. It can be seen from Examples 1-3 that the stronger the MO bond of the metal doped in the coating layer, the larger the spacing between the (002) crystal planes of the coating layer, the more stable the lattice of the coating layer, and the better the cycle stability of the positive electrode material. In addition, Examples 4 and 5 show that the battery capacity and cycle stability of the positive electrode material can be further improved by doping the core and / or coating layer of the positive electrode material with multiple elements.
[0101] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes a core and a coating layer coated on the surface of the core; the core includes LiNi a Co b Mn c M1 d O2, wherein 0.8≤a≤0.98, 0≤b≤0.1, 0.02≤c≤0.2, 0≤d≤0.005, a+b+c+d=1; the coating layer includes Li x V2O y and a doping element M2, wherein 0≤x≤1, 4≤y≤5; wherein M1 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W; wherein M2 is selected from one or more of B, Mg, Al, Ca, Ti, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W.
2. The positive electrode material according to claim 1, characterized in that The M1 is selected from one or more of Zr, Al and W; the M2 is selected from one or more of Ca, Al and Mg.
3. The positive electrode material according to claim 1 or 2, characterized in that The average primary particle size of the positive electrode material is 1 μm-10 μm.
4. The positive electrode material according to any one of claims 1 to 3, characterized in that The thickness of the coating layer is 5nm-50nm, and the mass of the coating layer is 0.15%-5% of the mass of the core.
5. The positive electrode material according to any one of claims 1 to 4, characterized in that The mass of the doping element M2 in the coating layer is the Li x V2O y The V element accounts for 2%-10% of the mass.
6. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The nickel source, the cobalt source, the manganese source, the core doping metal source and the lithium salt are mixed and calcined for the first time to synthesize the positive electrode material core; The cathode material core, the coating layer doped metal source and the vanadium source solution are mixed, and the obtained mixed solution is subjected to a hydrothermal reaction under acidic conditions to obtain a cathode material precursor; The positive electrode material precursor is dried, and then calcined for a second time to obtain the positive electrode material.
7. The method for preparing the positive electrode material according to claim 6, characterized in that: The nickel source, cobalt source and manganese source include Ni a Co b Mn c (OH)2、Ni a Co b Mn c O2 or a mixture of NiO, CoO and MnO in a mass ratio of a:b:c, wherein 0.8≤a≤0.98, 0≤b≤0.1, 0.02≤c≤0.2, a+b+c=1; the core doping metal source includes M1O x , wherein x is a number satisfying the conservation of chemical valence, M1 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W; the lithium salt comprises LiOH and / or Li2CO3; the coating layer doping metal source comprises M2Cl x 、M2(SO4) x and M2(NO3) x One or more of, wherein x is a number satisfying the conservation of chemical valence, and M2 is selected from one or more of B, Mg, Al, Ca, Ti, V, Sr, Y, Zr, Nb, Mo, Ag, In, Sn, Sb, Ba, La, Ce, Ta and W; the vanadium source solution comprises vanadium acetylacetonate and lithium metavanadate.
8. The method for preparing the positive electrode material according to claim 6 or 7, characterized in that: The ratio of the sum of the masses of Ni, Co and Mn elements in the nickel source, cobalt source and manganese source to the mass of Li element in the lithium salt is (Ni+Co+Mn): Li=1:1.01-1.1; the molar ratio of acetylacetonatovanadium and lithium metavanadate in the vanadium source solution is 1:1-1.3; the molar concentration of the lithium metavanadate in the vanadium source solution is 10mmol / L-80mmol / L; the mass of the lithium metavanadate in the mixed solution is 0.5%-5% of the mass of the core of the positive electrode material.
9. The method for preparing a positive electrode material according to any one of claims 6 to 8, characterized in that: The first calcination is a one-stage calcination or a two-stage calcination, the calcination temperature of the one-stage calcination is 780°C-950°C, the calcination time is 14h-20h, the heating rate is 5°C / min-10°C / min, and the calcination atmosphere is oxygen; the two-stage calcination includes pre-calcination and constant temperature calcination, the calcination atmosphere is oxygen, the pre-calcination temperature is 500°C-750°C, the pre-calcination time is 1h-6h, the constant temperature calcination temperature is 780°C-900°C, the constant temperature calcination time is 12h-20h, and the heating rate of the constant temperature calcination is 5°C / min-10°C / min; The calcination temperature of the second calcination is 350° C.-700° C., the calcination time is 6 h-18 h, the heating rate is 5° C. / min-10° C. / min, and the calcination atmosphere is oxygen.
10. The method for preparing a positive electrode material according to any one of claims 6 to 9, characterized in that: The pH value of the mixed solution under the acidic condition is 2-6; the reaction temperature of the hydrothermal reaction is 160°C-210°C, the reaction time is 12h-36h, and the heating rate is 5°C / min-10°C / min.
11. A positive electrode material obtained by the method for preparing a positive electrode material according to any one of claims 6 to 10.
12. A positive electrode of a battery, characterized in that: It comprises a conductive current collector and a positive electrode active material loaded on the conductive current collector, wherein the positive electrode active material comprises the positive electrode material according to any one of claims 1 to 5 or the positive electrode material prepared by the preparation method according to any one of claims 6 to 10.
13. A battery, characterized in that: The battery comprises a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, and the positive electrode comprises the battery positive electrode as claimed in claim 12.
14. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 13.